The Mediation of Tourist Engagement on The Effect of Destination Quality on Tourist Loyalty - Putri, Dhea Radika; Zamheri, Ahmad; Ridho, Sari Lestari Zainal; Paisal, Paisal; Africano, Fernando (AIBPM Publisher, 2022)
This study aims to examine and analyze: The effect of destination quality on tourist engagement, the effect of destination quality on tourist loyalty, the effect of tourist engagement on tourist loyalty and the effect of destination quality on tourist loyalty mediated with tourist engagement. The data analysis method uses a structural equation model. The research sample is tourists who have visited natural tourist destinations in South Sumatra totaling 320 respondents. The results of this study prove that the destination quality affects tourist engagement. Destination quality affects tourist loyalty. Tourist engagement affect tourist loyalty. Tourist engagement mediates the effect of destination quality on tourist loyalty. The implication of this finding explains that tourist engagement driven by destination quality will be able to increase tourist loyalty.